The Effect of Family Psychoeducation on Clients' Ability to Overcome Violent Behaviour - Gusdiansyah, Edo; Syarli, Setiadi; Ananda, Yuanita (REAL in Nursing Journal, 2025)
Background: Violent behaviour is a response to stressors that endanger themselves, others and the environment, until now it has not received appropriate treatment. Efforts made to overcome this are generalist and specialist nursing actions, one of which is family psychoeducation. This action can improve patient care skills and have a positive impact on families in managing stress. Purpose: This study aims to see the effect of family psychoeducation on clients' ability to cope with violent behaviour. Methods: The research method used was pre-experiment with One Group Pre Test-Post Test design. Data were collected through questionnaires with statements of nursing action implementation strategies (SP) 1-4 violent behaviour compiled by the researchers themselves based on Stuart's theory (2016), psychoeducation modules using family psychoeducation therapy modified from modules that have been developed by Nurbani (2009) with a sample of 30 families who have members with ODGJ in the Kuranji puskemas area. Data analysis used the T-Test test. Results: The results obtained before the family psychoeducation action showed the client's knowledge ability was an average of 18.91 (60.51%), namely the middle category, the client's psychomotor ability was an average of 12.34 (39.37%), namely the low category, after the family psychoeducation action showed the client's knowledge ability was an average of 67.38 (87.30%), namely the high category, the client's psychomotor ability was an average of 62.53 (85.43%), namely the high category. Conclusion: There is an effect of family psychoeducation on the client's ability to overcome the problem of violent behaviour (P=0.000). It is recommended that Puskesmas integrate family psychoeducation in mental health services by involving cadres and community leaders.